Clinical features of outpatients with allergic rhinitis at E.N.T. department, Faculty of Medicine, Gadjah Mada University/Dr. Dardjito General Hospital Yogyakarta - Supomo Sukardono Supomo Sukardono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
Clinical study was conducted on allergic rhinitls in ENT Department, DR. Sardjito Hospital for one year. The study included incidence, clinical symptoms, other test, and other treatment. The treatment having been conducted included allergen, desensitization and symptomatic therapy. Symptomatic therapy and allergen avoidance were the most often done